Stink and the attack of the slime mold - McDonald, Megan; Reynolds, Peter, 1961- (Somerville, Mass. : Candlewick Press, 2016)
Stink may be a super science freak, but even Dr. Stinkelstein is feeling freaked out about having a slime mold living and growing in his very own room. At Saturday Science Club, Stink learns that these one-celled organisms are smart enough to find their way out of mazes and gang up on food sources.
Keywords: Molds (Fungi) -- Juvenile fiction; Schools -- Juvenile fiction; Fungi -- Fiction; Schools -- Fiction